Surgical management of congenital cataract: the challenges - Pedrosa, C (2013)
Purpose: The surgical approach to congenital cataract in infants has been improved for the last decades although children may still develop deprivation amblyopia, strabismus, nystagmus and glaucoma. The authors show in video the surgical experience of micro-incision phacoemulsification in young children with congenital cataract highlighting the different challenges of this procedure. Setting/Venue: Dept. of Ophthalmology, Fernando Fonseca Hospital, Lisbon, Portugal. Methods: We present a series of 13 eyes in children with ages between 8 weeks and 4 years who underwent congenital cataract surgery, either unilateral (7 patients) or bilateral (3 patients). Micro-incision cataract surgery has shown to reduce intra- and postoperative complications and was performed in all operated eyes. Anterior capsulorrhexis was executed before main incision in all patients, which, according to our experience, avoids the instability of the anterior chamber, frequent in these cases. Primary posterior capsulotomy and anterior vitrectomy are important to reduce the prevalence of posterior capsule opacification, which is common in infants undergoing primary lens implantation, and were done in all operated eyes. A primary implantation of acrylic hydrophobic 3 pieces posterior chamber intra-ocular lens (IOL) was used with optic capture in most cases. Intracameral injection of preservative-free triamcinolone acetonide was performed, as it reduces anterior segment inflammation and improves vitreous visualization. Corneal main incision and side-ports were closed with non-reabsorbable suture. Results: In 2 cases IOL was implanted in the ciliary sulcus because of insufficient capsular support in the bag. We registered no other major intraoperative complications. Postoperative complications consisted of iris synechiae in 2 patients, one with the need of re-intervention for synechiolysis, and inflammatory reaction to the corneal suture in all cases, which resolved with the suture extraction. Intracameral triamcinolone injection intraoperatively did not affect intraocular pressure and no other adverse postoperative results were observed. Conclusions: Surgical approach to congenital cataract is challenging and several techniques may reduce the risks associated with this procedure. In our experience, a careful surgical approach with primary IOL implantation, even in infants, has shown good intra- and postoperative results.